FRI0080 Bone Mineral Density, Sclerostin and Insulin Are Independently Associated with Coronary-Artery Atherosclerosis in Patients with Established Rheumatoid Arthritis. (10th June 2014) - Bernardes, M.; Madureira, A.J.; Martins, M.J.; Vieira, T.; Gonçalves, D.; Pereira, J.G.; Machado, J.C.; Costa, L.; Ramos, I.; Simões-Ventura, F.; Martins, E.
Abstract : Background: Rheumatoid arthritis (RA) is associated with premature atherosclerosis and increased prevalence of cardiovascular disease (CVD). Inverse associations have been described between bone mineral density (BMD) and Coronary Artery Calcification (CAC) in different diseases. Objectives: To determine the degree of association of CAC Score (CACS) with bone density, bone markers and CVD risk factors in patients with established RA without known coronary disease, nor CV events. Methods: HAQ and DAS28 (4v) were obtained. ESR, CRP, traditional CVD risk factors, homocysteine, insulin, BNP, serum β-CTX1, osteocalcin, Dkk-1, sclerostin, RANKL and OPG were determined. BMD was assessed by DeXA (Lunar Expert® 1320) at the hip, lumbar spine and hands. CACS was evaluated using a 64-slice computed tomography scanner, Somatom Sensation Cardiac 64 (Siemens, Germany). Coronary calcium was measured by Argus software; CACS was determined by the Agatston score. A multivariate analysis model was used for statistical analysis (IBM SPSS Statistics 21). Results: We evaluated 57 RA patients, 42 (74%) women, age 54±12 years, disease duration 14±10 years, mean DAS28 (4v) of 4.15±1.24 and a mean HAQ of 1.32±0.69. In our sample, 29 (51%) were under biologics. CAC was detected in 31 (54%) patients (CACS ≤10: 37 (66%); 10< CACS ≤100: 10 (17%); CACS >100: 10 (17%). Lumbar spine, total hip, femoral neck, hands and second proximal phalanges BMD are inversely associated with CACS (p<0.05) after adjusting for age, disease duration, body mass index, DAS28 (4v), current HAQ, time under DMARDs therapy, years of corticosteroid use and years of bisphosphonates use. In terms of bone metabolism, lower levels of sclerostin were associated with higher CACS (p<0.05) (after adjusting for age, age at diagnosis, disease duration, body mass index, DAS28 (4v), current HAQ, current average daily dose of prednisone and years of bisphosphonates use). None of the traditional CVD risk parameters were associated with CACS. Insulinemia was inversely associated with CACS (p<0.001), after adjusting for age, age at diagnosis, disease duration, body mass index, DAS28 (4v), current HAQ, time under DMARDs therapy, time under biologics, years of corticosteroid use and current average daily dose of prednisone. Conclusions: Our RA population reproduced the inverse relationship between, either systemic or localized, BMD and CAC, supporting the hypothesis that bone metabolism and atherosclerotic plaque mineralization are related processes. As in the african american-diabetics, sclerostin was negatively associated with CACS in our RA patients. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3921